2010
DOI: 10.1016/j.ejcts.2009.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the utility of vibration response imaging device and Operation Planning Software in the assessment of patients before lung resection surgery☆

Abstract: VRI(XP) O-Plan has shown high accuracy in predicting postoperative FEV(1) after lung resection surgery. Given its simplicity of operation and the non-invasive nature of VRI(XP) and O-Plan, it could be a good alternative to perfusion scan in pre-surgery assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…sounds during spontaneous breathing [7,8] and demonstrated similar results for both methods. We undertook a prospective multicenter study at 6 United States sites to validate whether quantitative lung sound measurements are a simpler alternative to radionuclide tests for estimation of postoperative lung function in this patient population.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…sounds during spontaneous breathing [7,8] and demonstrated similar results for both methods. We undertook a prospective multicenter study at 6 United States sites to validate whether quantitative lung sound measurements are a simpler alternative to radionuclide tests for estimation of postoperative lung function in this patient population.…”
supporting
confidence: 81%
“…Recordings with artifacts were excluded. The "O-Plan" software automatically calculates each lung's total vibration energy Ϯ standard deviation as an average of 2 or more goodquality recordings of the respiratory cycle [8]. The standard deviation provides feedback on the reliability of the recorded data.…”
Section: Lung Function Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has wide prospect in clinical application. Previous studies were focused on the characteristics of VRI images of healthy populations and evaluation of equipment performance and pneumonectomy and mechanical ventilation were mainly involved for diseases (5–8), were mainly on airflow limited diseases (8,9). However, there were few literature reports that applied this technology in infectious diseases of the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Vibration response imaging (VRI) is a new, noninvasive, simple to use technique that can provide an accurate estimate of ppoFEV1. 4 In a previous study by Jimenez and colleagues, 5 VRI-based measures have shown high accuracy in the prediction of ppoFEV1.…”
mentioning
confidence: 92%